2012
DOI: 10.1002/anie.201200516
|View full text |Cite
|
Sign up to set email alerts
|

Facile Bucky‐Bowl Synthesis by Regiospecific Cove‐Region Closure by HF Elimination

Abstract: Building bowls: An effective intramolecular aryl–aryl coupling is the key step in rational fullerene synthesis and in synthesis of extended buckybowl structures. Such a process can be embodied very efficiently through quantitative HF elimination on active Al2O3. The process is characterized by an unprecedentedly high chemoselectivity and regiospecificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
95
0
11

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(110 citation statements)
references
References 27 publications
4
95
0
11
Order By: Relevance
“…It has been shown that fluorine acts as an effective activating group provoking highly selective intramolecular ring closures by HF elimination under FVP conditions [12] and catalytically. [13] In this communication we demonstrate that a specially fluorinated C 60 fullerene precursor can be folded into the fullerene cage very effectively under laser desorption/ionization (LDI) conditions at rather low laser fluence. In contrast to the non-activated precursor, the laser induced cyclization in the title compound can be realized highly selectively without any detectable side reactions or undesired fragmentations.…”
mentioning
confidence: 88%
“…It has been shown that fluorine acts as an effective activating group provoking highly selective intramolecular ring closures by HF elimination under FVP conditions [12] and catalytically. [13] In this communication we demonstrate that a specially fluorinated C 60 fullerene precursor can be folded into the fullerene cage very effectively under laser desorption/ionization (LDI) conditions at rather low laser fluence. In contrast to the non-activated precursor, the laser induced cyclization in the title compound can be realized highly selectively without any detectable side reactions or undesired fragmentations.…”
mentioning
confidence: 88%
“…1. The mechanism previously proposed for Al 2 O 3 mediated HF elimination in fluoroarenes via an aromatic transition state, 20 can be excluded, since in this case no carboxylic acid formation is expected. The intense coloring of the alumina phase indicates that the reaction passes through the formation of a carbenium ion, generated as a result of heterolytic C-F bond dissociation typical for Lewis acid mediated C-F bond activation.…”
mentioning
confidence: 88%
“…Moreover, it has been found that intramolecular Aryl-Aryl coupling of fluoroarenes via γ-aluminum oxide-mediated C─F bond activation can be realized under mild conditions with unprecedentedly high chemoselectivity [25,26]. Using this technique an extended bowlshaped PAHs representing more than 75% of the C 60 fullerene connectivity was obtained with close to quantitative yield (Figure 4) [24], demonstrating high potential for generating extended nonplanar carbon-based nanostructures including fullerenes. Although the rather big fullerene fragments can be successfully produced by wet-chemical methods, the solutionsynthesis of fullerenes remains a challenge.…”
Section: Wet-chemical Synthesismentioning
confidence: 91%
“…The recent discovery of effective intramolecular aryl-aryl coupling via C-F bond activation under transition-metal free conditions might be a solution to this problem. Recently, Siegel et al [21], Ichikawa et al [22], and Amsharov et al [23,24] have demonstrated the efficiency of the C─F bond activation strategy for the synthesis of various bowl-shaped PAHs via formal HF elimination step (cyclodehydrofluorination). In the last case, the effective cyclization was achieved utilizing easily accessible aluminum oxide, which makes the approach highly attractive for preparative-scale synthesis.…”
Section: Wet-chemical Synthesismentioning
confidence: 99%
See 1 more Smart Citation